Corrosion Control Mechanisms and the Effect of pH on Corrosion in the Crude Oil Refining Process - Mohammed, Karrar A. (Journal of Petroleum Research and Studies, 2022)
The consequences of corrosion in the crude oil refining process cannot be ignored due to the damage caused by the corrosion of oil equipment, and the serious losses that result from that. Therefore, in this research, methods of controlling the occurrence of corrosion in the crude oil refining unit in the Najaf refinery for four types of crude oil - API (28, 28.2, 29.2, and 30.2) were studied. Chemicals were added in different quantities and types before and during the crude oil refining process to the atmospheric distillation unit, where it was found that these chemicals have the ability to make a media within the limits of pH from 5.5 to 6.5, where the corrosion became little or no. Also, an anti-corrosion chemical was added, which reduced the incidence of corrosion in the overhead systems of crude oil refining equipment. In addition to treating the crude oil using desalter before refining it, where the mud and dirt and a large proportion of the salts in the emulsified water were removed from crude oil. The best results obtained were pH (6, 6, 5.7, and 5.5) and the percentage of iron ions Fe+2 ( 0.8, 1, 1.5, and 2.1) for four types of refined crude oil at using pump dosages for inhibitor (2.5, 2, 3.5 and 3.5), caustic soda (4, 6, 8, and 8) and neutralizer (2, 2.5, 3, and 3). This practical study showed the importance of adding chemicals in different quantities, as well as electrical and thermal treatment in controlling and preventing corrosion of oil equipment in the crude oil refining unit.